ESPECIALLY OF PREPARATION NATURAL - Симоненко, Наталья; Ильченко, Яна; Билька, Марима; Войцеховский, Владимир; Матвиенко, Андрей; Рак, Александр; Мулярчук, Оксана (SWorldJournal, 2021)
The article describes the technology of production of natural fruit alcoholic beverages are present. Systematized and concentrated material for the preparation of raw materials for processing. The conditions for obtaining a quality drink are described in